2016
DOI: 10.1002/ceat.201600163
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐Flow Synthesis and Functionalization of Magnetite: Intensified Process for Tailored Nanoparticles

Abstract: The spinning disc reactor (SDR) is used for the size‐selective synthesis and functionalization of nanoscale superparamagnetic iron oxide particles in a single‐step continuous‐flow process. Nanometer‐sized magnetite (Fe3O4) particles are precipitated in a highly sheared thin liquid film on a rapidly rotating disc. A novel liquid‐liquid synthesis is presented whereas control over particle size is reached via adjustable micromixing properties on the disc. The nanoparticles with tailored size, narrow size distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The importance of mixing conditions for the IONP size distribution (with smaller but more monodisperse particles obtained with faster mixing) is well documented [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of mixing conditions for the IONP size distribution (with smaller but more monodisperse particles obtained with faster mixing) is well documented [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 For example, Baumgartner et al showed with cryo-transmission electron microscopy (TEM) the formation of amorphous ferrihydrite which attaches to the surface of the growing IONP. 15 However, most co-precipitation syntheses proceed via a single and abrupt increase in pH, which is also the most common approach for large-scale and continuous reactor systems 14,[18][19][20][21] due to the shorter process times. Hence, the understanding of the abrupt pH transitions is extremely important.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Also, fast mixing has been shown to promote the synthesis of small IONPs. [28][29][30] Alternatively, small IONPs for MRI can be produced via rapid (microwave) heating of a FeCl 3 and trisodium citrate solution together with the reducing agent hydrazine. 31,32 The route for IONP T 1 contrast agents to reach market maturity is long and brings challenges, not only for chemists, but also engineers and entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%